Treatment outcomes of squamous cell carcinoma of the external auditory canal and potential benefit of induction chemotherapy followed by chemoradiotherapy - Mizunari, Yosuke; Nagaoka, Masato; Takeshita, Naohiro; Kanno, Kazuki; Hirayama, Haruyuki; Akutsu, Taisuke; Kessoku, Hisashi; Ishida, Katsuhiro; Yamamoto, Yutaka (Frontiers in Oncology, 2025)
IntroductionCarcinoma of the external auditory canal (EAC) is rare, and squamous cell carcinoma (SCC) is the most common histological type. There are few reports on the treatment outcomes for a large number of cases at a single institution, and a standard treatment has not been established.MethodsTreatment details and prognoses were retrospectively examined for patients who underwent primary treatment for SCC of the EAC at The Jikei University between April 2015 and May 2023.ResultsTwenty-seven patients with SCC of the EAC were included (median age of 64 years). Analysis using the revised Pittsburgh classification revealed that there were 3 cases of T1, 4 cases of T2, 9 cases of T3, and 11 cases of T4. Among the patients, 13 were treated surgically, 1 underwent partial resection of the EAC, 11 underwent lateral temporal bone resection, and 1 underwent subtotal temporal bone resection. The remaining 14 patients received nonsurgical treatment: 1 with radiotherapy, 3 with concurrent chemoradiotherapy, and 10 with induction chemotherapy (ICT). The overall survival (OS) and disease-free survival (DFS) rates at 3 years were 72.8% and 50.5%, respectively. When the surgical and non-surgical groups were compared, the 3-year OS and DFS rates were 92.3% and 68.3% for those who underwent surgery and 47.6% and 35.7% for those not treated with surgery, respectively, suggesting a better prognoses for patients who underwent surgical treatments (p = 0.045, 0.052). In the non-surgical group, the 3-year OS and DFS rates were 90.0% and 50.0% for those who received ICT and 0% and 0% for those who did not receive ICT, respectively, indicating better prognoses for patients treated with ICT (p = 0.0075, 0.0012).ConclusionAt our institution, the 3-year OS and DFS rates of patients with SCC of the EAC were favourable for those who underwent surgery and received ICT. These findings suggest that treatment outcomes can be improved by using ICT in nonsurgical treatments for patients with SCC of the EAC.